The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae) Part III: the C. henryi species group, with the description of three new species - Palacio, Edgard; Bordera, Santiago; Díaz, Francisco (Zootaxa, 2019)
The New World Clistopyga henryi species group is revised. Three species are described as new: C. carinata sp. nov., C. declinata sp. nov., and C. teresitae sp. nov. An illustrated identification key to Neotropical species of the group is provided. The Clistopyga henryi species group is composed of species with polished, and straight or down-curved ovipositors.